1997
DOI: 10.3758/bf03206014
|View full text |Cite
|
Sign up to set email alerts
|

Agonistic sensory effects of airborne chemicals in mixtures: Odor, nasal pungency, and eye irritation

Abstract: Threshold responses of odor, nasal pungency (irritation), and eye irritation were measured for single chemicals (Lpropanol, l-hexanol, ethyl acetate, heptyl acetate, 2-pentanone, 2-heptanone, toluene, ethyl benzene, and propyl benzene) and mixtures of them (two three-component mixtures, two sixcomponent mixtures, and one nine-component mixture). Nasal pungency was measured in subjects lacking a functional sense of smell (i.e., anosmics) to avoid interference from olfaction. Various degrees of stimulus agonism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 22 publications
6
55
0
Order By: Relevance
“…In environmentally realistic conditions people can be exposed for long periods (from hours or days up to months or even years) to low-levels of dozens of airborne chemicals. A comprehensive understanding of chemosensory detection needs to elucidate the effects of stimulation time, e.g., olfactory adaptation 33 and chemesthetic sensitization/adaptation 34 , as well as the effects of mixtures of chemicals 35 . …”
Section: Resultsmentioning
confidence: 99%
“…In environmentally realistic conditions people can be exposed for long periods (from hours or days up to months or even years) to low-levels of dozens of airborne chemicals. A comprehensive understanding of chemosensory detection needs to elucidate the effects of stimulation time, e.g., olfactory adaptation 33 and chemesthetic sensitization/adaptation 34 , as well as the effects of mixtures of chemicals 35 . …”
Section: Resultsmentioning
confidence: 99%
“…showed a cut-off effect (16). No pungency could be detected by anosmics for homologs above propyl benzene (12).…”
Section: Procedurementioning
confidence: 93%
“…Previous work has addressed alcohols, acetates, ketones, alkylbenzenes, aliphatic aldehydes and carboxylic acids (9)(10)(11)(12)(13)(15)(16)(17). Along homologous series, physicochemical properties change systematically, and carbon chain length represents a convenient "unit of change" against which to analyze sensory results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies of sensory irritation thresholds (NPTs and EITs) from mixtures of VOCs have shown various levels of additivity that, to a first approximation, are not-too-far from complete additivity (Nielsen et al, 1988;Cometto-Muñiz et al, 1997;1999;2001a;2004a;2004b). So are results from studies on ODTs 2005b;Wise et al, 2007;Miyazawa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%